Genetic and environmental effects on weaning weight in crossbred beef cattle (Bos taurus × Bos indicus) - Dominguez-Castaño, P. [UNESP]; Maiorano, A. M. [UNESP]; De Oliveira, M. H.V. [UNESP]; Dos Santos Correia, L. E.C. [UNESP]; Silva, J.A.Ii.V. [UNESP] (My University, 2021)
This work aimed to evaluate the effects of sire's and dam's biological type, dam's age class at calving and individual heterozygosis, and to estimate variance components for weaning weight adjusted to 210 days (WW210) in beef cattle of different breed groups. Records of 13 687 animals, obtained from 2000 to 2007, were used. Bulls from the biological types Zebu (N), Adapted (A), British (B), Continental (C) and 1/4N|1/4A|1/4B|1/4C were mated with purebred zebu (N) and crossbred females (1/2C|1/2N and 1/2B|1/2N). Dam age at calving was 3-12 years. The influence of several effects on WW210 was tested using the least square method. Variance component analysis was performed using a Bayesian approach. The model included contemporary group, dam's age class at calving, sire's and dam's biological types as systematic effects, animal's age and individual heterozygosis as linear covariates, and direct and maternal additive genetic, maternal permanent environmental and residual effects as random effects. The progeny of bulls from biological type B and the crossbred cows showed higher WW210 means. Cows at 6-7 years old weaned heavier calves. Direct and maternal heritability estimates for WW210 were 0.5 ± 0.04 and 0.1 ± 0.02, respectively. Calves with 100% individual heterozygosis weighed on average 25.98 kg more at weaning compared to progenies from pure breeds. Sire's and dam's biological types influence the WW210 of the crossed progenies. Crossbred cows produce heavier calves compared to biological type N cows. These results and the obtained direct and maternal heritabilities suggest it is possible to choose the lines of sires and dams that could be used to make the crosses to obtain progenies with better performance for WW210.
Keywords: Crossbreeding; heterozygosis; maternal ability; pre-weaning growth